Car park sharing application - Seah, Noah Kaixian (Nanyang Technological University, 2023)
In the United Kingdom, the high cost of parking and low availability is a growing concern. This has pushed motorists away from driving despite having owned a vehicle. While there are existing applications to tackle the issue, users have raised concerns and difficulties when using these applications. Hence the project will develop a mobile application that connects car park providers and motorists. Car park providers may list their available car parks for rent to earn extra income, while motorists may search for their desired car park lots based on location, price, duration and timing. The app intends to increase the supply of parking lots, hence reducing the cost of parking and make parking more accessible to motorists.